‘Voices’ in the Courtroom. The role of notaries in the ‘Inquisitorial autobiography’ - José Luis Loriente Torres (Culture & History Digital Journal)
Little is known about the workings of Inquisitorial notaries during the early modern period, particularly regarding their documentation methods within the courtroom. This paper aims to analyze the procedures they employed in documenting proceedings. Questions arise regarding how they managed to transcribe what was happening in the courtroom, the accuracy of their records, and the mechanisms employed in carrying out this function. An analogy often invoked is whether these sources can convey the ‘voices’ of defendants. Here, it will be argued that the ‘voice’ modern readers ‘hear’ is that of the notary, who lends it to the defendant. Due to the absence of explicit information in any manual or instruction, we will directly examine the Inquisitorial proceedings. Specifically, we will focus on the first hearing, audience, or interrogation, known as ‘Primera Audiencia’, during which all defendants were obligated to declare their life stories or ‘discurso de su vida’ from 1561 onwards. Both the first interrogation and the life narrative were the most formulaic and fixed part of the trial, inviting comparation. Although we have focused on these specific elements, some of our conclusions may apply to the rest of the process. Our methodology will involve studying inks, handwritings, and micro-expressions.